Marriage, manners, and mobility in early modern Venice - Cowan, Alexander (Historical urban studies, 2007)
Noble status and social differentiation in early modern Europe -- The Avogaria investigations -- Outsider brides and their families -- Huomini civili and patrician marriage -- The social dimensions of acceptability -- Concubines and natural daughters -- Gender, honourable, and dishonourable behaviour -- Marriage and the patriciate -- Conclusion